Connecting Castings for Operation under Conditions of Cyclic Temperature Changes - Drotlew, Andrzej; Piekarski, Bogdan (Journal of Casting & Materials Engineering, 2020)
The separable connections used in technological equipment of heat treatment furnaces (OTP) are described in this study. The equipment is used for the heat treatment of charges, i.e. for the thermal and thermo-chemical treatment of parts of machines and devices. OTP is used for the charge formation and its transport before, during and after heat treatment operations. Accessories of this type are usually compact structures composed of several or several dozen cast elements. The main components are grates and pillars, which form an outer contour of the OTP and also allow for the correct arrangement of heat-treated parts. To form a relatively rigid structure composed of the grates and pillars, it is necessary to join these components together. For this purpose, various types of separable connections are used, mainly of a cylindrical shape with threaded parts. The subject of this study is focused on the construction and operating conditions of typical OTP structures, as well as the methods of fastening the pillar in a grate, i.e. on the design of the bottom part of the pillar and the hole in the grate in which this pillar is embedded.